Representasi Penulisan Berita Efektif Pada Teras Berita Surat Kabar (Analisis Wacana Pada Film The Bridgerton) - Fitri Nur Ardiantika (Program Studi Penerbitan, Politeknik Negeri Jakarta, 2024)
The Bridgerton film is a British film based on a novel by Julia Quinn, who is known as a writer of historical romance stories. The Bridgerton takes place in England during the Regency era, namely around the 1800s. This film depicts the life of British aristocrats during the Regency Era in England which lasted from 1811 – 1820. The main characters in this film are the Bridgerton family and the writer of the newspaper